Advances in reliability and system engineering - Ram, Mangey; Davim, J. Paulo (Springer, 2017)
This book presents original studies describing the latest research and developments in the area of reliability and systems engineering. It helps the reader identifying gaps in the current knowledge and presents fruitful areas for further research in the field. Among others, this book covers reliability measures, reliability assessment of multi-state systems, optimization of multi-state systems, continuous multi-state systems, new computational techniques applied to multi-state systems and probabilistic and non-probabilistic safety assessment.
Keywords: Systems engineering.; Reliability (Engineering); elektronické knihy; electronic books